DNA Identification from Sebaceous Sweat Fingerprint Deposits on Corpse Integuments - Tat’yana G. Faleeva; Igor’ V. Kornienko; Igor’ N. Ivanov; Semen M. Kuz’menko; Evgenii S. Mishin; Dmitrii V. Shatov; Boris V. Kovalev; Anna A. Chebotareva; Ekaterina N. Hodareva (Теория и практика судебной экспертизы)
The paper presents the results of a pilot molecular genetic study of sweat and oil residue left by the fingertips and hand palms of male volunteers (donors) on various regions of the skin surface of dead bodies (recipients) of both sexes. In cases of contact with female recipients donor-specific allele combinations were obtained for only 11.6% of autosomal loci and 12.9% of Y-chromosomal loci. Donor-specific traits were absent in 68.4% of autosomal loci and 87.1% of Y-chromosomal loci. In cases of contact with male recipients the full genetic profile was obtained for 18.6% of autosomal loci, and 64.2% of loci showed a lack of donor-specific alleles. Meanwhile, allelic combinations specific to female recipients were encountered in 40.5% of autosomal loci, and to male recipients – in 34.2% of autosomal loci. Results demonstrate poor adhesion of sweat and oil compounds from donors’ hands to the corpses’ skin, probably due to significant temperature differences between contact surfaces.